2019
DOI: 10.4314/jae.v23i4.7
|View full text |Cite
|
Sign up to set email alerts
|

Soil Conservation and Water–Resources Management Techniques used by Small- Scale Rice Farmers in Ebonyi State, Nigeria

Abstract: The study assessed s soil conservation and waterresources management techniques among small-scale rice farmers in Ebonyi State. A sample of 130 respondents generated via multi-stage, purposive and simple random methods were used. Data were generated through questionnaire and interview schedule and analysed using percentage and mean. Results, showed the indigenous methods for soil and water-resources management used by the rice farmers to include: construction of basin and flow walls ( = 92.3%), construction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Finally, vegetative practices adopted included planting Napier grass, planting selected trees, and grass stripes. Obinna [28] reported that trees and bunds were particularly popular among rice farmers. Results from all the three catchments suggest that there was a predominance of terrace use as a soil and water conservation approach.…”
Section: Soil Erosionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, vegetative practices adopted included planting Napier grass, planting selected trees, and grass stripes. Obinna [28] reported that trees and bunds were particularly popular among rice farmers. Results from all the three catchments suggest that there was a predominance of terrace use as a soil and water conservation approach.…”
Section: Soil Erosionmentioning
confidence: 99%
“…This was attributed to farmers having small farm sizes, ranging from a mean of 1.11 acres for females to 2.49 acres for males, thus contributing to intensive use, over-cultivation, lack of crop rotations, and hence soil mining. Rice farmers in Nigeria used compost manuare and crop rotation to maintain fertility [28]. Other farmers in Wundanyi used soil degrading inorganic fertilizers, like phosphorus-based fertilizers that have a long residue effect, for a prolonged period in the past.…”
Section: Declining Soil Fertilitymentioning
confidence: 99%
“…Ebonyi state is renowned for its massive agricultural activities, and the farmers in the state have benefited from FAO training on different agricultural practices [26]. Obinna [27] identified crop rotation as an indigenous practice in the state, but there is little or no proof to show the level of adoption of crop rotation among farmers in Ebonyi state. This study, therefore, assessed the crop rotation and diversity practices among rural farmers of Ebonyi State, Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Resources are crucial to achieve the goal of a company whether that be finishing a task or a project or helping an individual business owner to examine the important task to evaluate within a project. Thus "resource management techniques" are all about the visibility of a project, so that a project manager can be able to see, observe and retain the required things which can help a project to be executed in a proper manner [2]. There are several types of importance of business resource management which are actually immensely reluctant to depict the successful execution of a project.…”
Section: Introductionmentioning
confidence: 99%